2013
DOI: 10.1371/journal.ppat.1003742
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Adenovirus E4orf4 Protein Binding Site on the B55α and Cdc55 Regulatory Subunits of PP2A: Implications for PP2A Function, Tumor Cell Killing and Viral Replication

Abstract: Adenovirus E4orf4 protein induces the death of human cancer cells and Saccharomyces cerevisiae. Binding of E4orf4 to the B/B55/Cdc55 regulatory subunit of protein phosphatase 2A (PP2A) is required, and such binding inhibits PP2AB55 activity leading to dose-dependent cell death. We found that E4orf4 binds across the putative substrate binding groove predicted from the crystal structure of B55α such that the substrate p107 can no longer interact with PP2AB55α. We propose that E4orf4 inhibits PP2AB55 activity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…icity of E4orf4 when it is expressed in cancer cells at levels much higher than those detected normally during infection, when such effects would not be expected to occur (7). They were consistent with earlier studies indicating that E4orf4 can affect mitosis.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…icity of E4orf4 when it is expressed in cancer cells at levels much higher than those detected normally during infection, when such effects would not be expected to occur (7). They were consistent with earlier studies indicating that E4orf4 can affect mitosis.…”
supporting
confidence: 91%
“…Nevertheless, E4orf4 expression also rapidly resulted in cell rounding, a hallmark of early mitosis, suggesting that E4orf4 might induce early mitotic events but create problems with normal passage through and exit from mitosis. In this context, it should be remembered that E4orf4 was shown to bind to the putative substrate binding groove of the B55 regulatory subunit of PP2A (7,21), thus inhibiting PP2A B55 activity by interfering with the access of substrates to the holoenzyme (7,9). Interestingly, such inhibition may mimic a natural process for entry into mitosis regulated by Greatwall (Gwl) and endosulfine alpha (ENSA), which are involved in the control and timing of M phase (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Earlier work indicated that a major target responsible for E4orf4 toxicity in both human and yeast cells is the B55/Cdc55 regulatory subunit of PP2A (6,16,18,(20)(21)(22)(24)(25)(26)(27)(28). Our recent studies indicated that binding of E4orf4 to B55␣ blocks activity against at least some substrates, and we believe that the failure to dephosphorylate critical substrates involved in regulation of the cell cycle causes growth arrest and subsequent cell death (17,53). Previous results in yeast suggested that APC may be a target for E4orf4 (25), and we have shown, also in yeast, that expression of E4orf4 prematurely induces the early mitotic form of APC Cdc20 and inhibits activation of the late mitotic/early G 1 form APC Hct1/Cdh1 (27).…”
Section: Discussionmentioning
confidence: 92%
“…The E4orf4 polypeptide shares little homology with any known eukaryotic protein; however, two of its major cellular targets have been identified. Events in the nucleus appear to result largely from an interaction with B55 regulatory subunits of protein phosphatase 2A (PP2A) (6,(16)(17)(18)(19)(20)(21)(22) that we have shown in the case of B55␣ blocks the activity of PP2A against at least some substrates (17,53). E4orf4 is also toxic in yeast (Saccharomyces cerevisiae), and this effect is largely abrogated in yeast lacking CDC55, the B55 ortholog (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 88%
“…Furthermore, overexpression of the PP2A-B55 subunit was reported to enhance E4orf4-induced cell death (18). In contrast, it was recently suggested that E4orf4 induces cell death by titrating out functional PP2A holoenzymes containing the B55 subunit, thus preventing dephosphorylation of substrates required for cell survival (22). It was also demonstrated that E4orf4 inhibited PP2A activity toward some substrates but not toward oth-ers (23).…”
mentioning
confidence: 99%